Factors affecting resilience in pregnant Lebanese women exposed to overlapping crises - Maya Bizri; Sima Fatima Sharafeddin; Duaa Fahs; Hala Itani; Ghida Kassir; Ghina Ghazeeri (BMC Psychology)
Abstract Background Resilience is a critical determinant of individuals’ psychological well-being and their ability to cope with adversity. Resilience has emerged as a point of clinical relevance when addressing the effects of extreme environmental adversity on vulnerable populations. Lebanon experienced an economic collapse, the COVID-19 pandemic and the Beirut Blast within the span of a single year, causing significant lasting damage. Pregnant women were particularly vulnerable during this period of time. This study aims to measure the resilience of pregnant women in Lebanon after exposure to multiple, large-scale traumatic events. It also examines the potential effect of obstetrical factors, perceived stress, perceived social support, and childhood experiences on resilience scores. Methods We conducted a cross-sectional study among Lebanese pregnant women. A total of 257 pregnant Lebanese women who resided in Lebanon during all three crises were recruited to participate. Resilience, adverse and benevolent childhood experiences, and perceived social support were measured using validated scales: the Connor-Davidson Resilience Scale, the Adverse Childhood Experiences questionnaire, the Benevolent Childhood experiences scale, and the Multidimensional Scale of Perceived Social Support respectively. We also included a section on perceived stress, which included questions about the impact of the COVID-19 pandemic, the economic crisis, and the Beirut blast. Results Our findings revealed a significant negative correlation between resilience and perceived stress (b=-0.157), suggesting resilience’s protective role against the negative impact of stress during pregnancy. Furthermore, a positive correlation was demonstrated between perceived social support and resilience (b = 0.19), underscoring the importance of supportive networks in boosting resilience. Conclusion This research contributes vital knowledge to the understanding of resilience during the perinatal period. It emphasizes the need for comprehensive prenatal care that incorporates social and psychological support, thereby enhancing resilience and overall well-being in pregnant women amidst the multifaceted challenges faced in Lebanon.